PUBLIKASI ILMIAH DAN PLAGIARISME DENGAN LOCUS OF CONTROL SEBAGAI MODERASI - Isnaini Anniswati Rosyida; M. Nizarul Alim (J-MACC, 2022)
This study aims to determine the effect of scientific publication requirements on plagiarism and the role of locus of control as a moderating variable from the influence of scientific publication requirements on plagiarism in private universities. This research uses a quantitative method with respondents from accounting lecturers at Private Universities in East Java. The researcher used the Smart PLS 3.0 program to test the research hypothesis to examine the effect of scientific publication requirements on plagiarism and examine the role of locus of control as a moderating variable from the influence of the burden of scientific publications on plagiarism. The sample in this study is a lecturer at a Private College in East Java. The method used to determine the sample is purposive sampling. The research data was obtained by distributing questionnaires directly to the respondents. The test results show that the burden of scientific publications influences plagiarism. Locus of control is a moderating variable from the influence of the burden of scientific publications on plagiarism on accounting lecturers in private universities